2018
DOI: 10.1080/16089677.2018.1541211
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perceptions of dietary and related self-management challenges and education programme preferences for type 2 diabetes adults

Abstract: To inform the adaptation of an intervention from a primary healthcare setting to a tertiary setting, the dietary and related self-management challenges and education programme preferences of adults with type 2 diabetes (T2DM) were explored. Setting: A study was undertaken in a tertiary teaching hospital in Gauteng Province, South Africa. Methods: A qualitative approach was employed. Data were collected via focus-group discussions and open-ended selfadministered questionnaires from a convenient purposive sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…The results from the HPs and patients related to self-care challenges and preferences for diabetes NEP were similar in most cases 28 and comparable to those of the original NEP. 20 Briefly, regarding self-care challenges the needs assessment revealed that patients (i) experienced knowledge deficits, (ii) struggled with adhering to diet (portion control, low consumption of vegetables and fruits, inappropriate dietary choices, irregular meals, and problems with balancing diet and insulin), exercise, medication and appointment keeping, and (iii) they faced multiple barriers to self-care (financial constraints, unsupportive social and physical environments, and personal factors).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The results from the HPs and patients related to self-care challenges and preferences for diabetes NEP were similar in most cases 28 and comparable to those of the original NEP. 20 Briefly, regarding self-care challenges the needs assessment revealed that patients (i) experienced knowledge deficits, (ii) struggled with adhering to diet (portion control, low consumption of vegetables and fruits, inappropriate dietary choices, irregular meals, and problems with balancing diet and insulin), exercise, medication and appointment keeping, and (iii) they faced multiple barriers to self-care (financial constraints, unsupportive social and physical environments, and personal factors).…”
Section: Resultsmentioning
confidence: 58%
“…They also perceived the challenges to greatly impact on their quality of life. 28 Regarding preferred characteristics of the NEP, the needs assessment revealed the following. Participants would prefer (i) monthly education meetings coinciding with collection of medication; (ii) content on self-discipline for lifestyle behaviours (diet and exercise), content on diabetes basics, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The findings support other studies that have attempted to understand and address the challenges of working within adult diabetic populations. 28-30 Moreover, while most studies in Ghana to date have focused essentially on factors such as patients’ demographic characteristics (e.g., age, gender, education, and religion) diet and body weight that are associated with adherence to recommended self-care behaviours 17,18 ; few qualitative studies have been undertaken to explore the multiple facilitators and barriers pertinent to the self-care of T2D. This study therefore adds to the rather sparse literature in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study in Baghdad, Iraq, found that although patients properly adhered to anti-diabetic medications, most patients reported having a self-management deficit due to a lack of proper information/knowledge and needing face-to-face educational sessions [ 36 ]. A study in South Africa also reported that a diabetes-related knowledge deficit was the main barrier for effective self-management, for which patients desired a monthly DEP with strategies for motivating and sustaining program participation (e.g., testimonials from successful participants) along with family support [ 37 ]. A content analysis study in Malawi also revealed that patients had a positive regard for diabetes education sessions [ 5 ].…”
Section: Discussionmentioning
confidence: 99%